Contextual Islamic Theology – Contemporary (A Study of Hasan Hanafi's Contextual Theology) - Deswita Deswita; Hidayatul Azizah Gazali (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2022)
In the development of modernity, Religion is often criticized, which then in response to that criticism, people began to question again and look for the most authentic relationship between religion and modern problems. The response appears in various forms of renewal of religious understanding based on the context that occurs. Among the forms of renewal, it is colored by the emergence of Hasan Hanafi's contextual theology with liberation theology, Modernist Theology that desires to modernize the Muslims, trans formative theology that wants to realize the transformation of Muslims societies and inclusive theology that invites Muslims to live an Inclusive religious life, tolerance and respect for religious pluralism. This research is library research with a focus on contemporary contextual theology. Data is collected through documentation techniques that collect data contained in various books, printed journals and online journals. The data that the author has collected was then analyzed deductively. From this research, it can be concluded that this contextual theology talks about God and His relationship with humans both based on revelation and reason. While contemporary theology is theological thoughts that emerged in contemporary times, which emerged to modernize or advance Muslims, realizing the transformation of Muslim society so that they can achieve progress, and the development of religious understanding and life that is inclusive, tolerant, and respectful of religious pluralism.